7 - « L’histoire de l’eau » et la dynamique politique, sociale et culturelle du Nord du Cameroun - Armel, Sambo (Africa Development, 2023)
This article presents the role and place of water in the history of societies in northern Cameroon. It aims to show the importance of water as an object of study to understand the organisation, the dynamics and the evolution of these societies. This article is based on interviews, life stories, observation of the relationships that societies have with water and the use of written data (archives, reports, scientific works, etc.). The compilation of all these sources allowed to outline a 'history of water' in the northern part of Cameroon. Thus, water is at the origin of migrations and the choice of settlement sites for populations. It occupies an essential place in social organisation, cultural practices and symbolises political power. Initially a common good for societies, it has become a source of conflict between individuals and communities.